Cancer incidence in a cohort of Swedish sewage workers: extended follow up. Issue 10 (1st October 1999) - Friis, L; Mikoczy, Z; Hagmar, L; Edling, C
Abstract : OBJECTIVES: To study the cancer incidence in a cohort of Swedish sewage workers. An increased incidence of cancer of the stomach, the kidney and the nervous system in this cohort was previously reported. This new analysis reports on 9 more years of follow up. METHODS: The study is an analysis of a cohort of all 711 employees at 17 Swedish sewage plants employed for at least for 1 year during the years 1965-86. Assessment of exposures was performed by classification of work tasks. Standardised incidence ratios (SIRs), and 95% confidence intervals (95% CIs) were calculated. RESULTS: The total cancer incidence was not significantly increased (SIR = 1.2, 95% CI 0.92 to 1.5) but the incidence of prostate cancer was (SIR = 1.6, 95% CI 1.0 to 2.5), and based on two cases only, there seemed to be a significant increase of cancer of the nose and the nasal sinuses (SIR = 12, 95% CI 1.5 to 44). The incidence of stomach cancer was also increased (SIR = 2.3, 95% CI 0.99 to 4.5). There was no relation between cancer incidence and level of sewage exposure. CONCLUSIONS: Sewage workers did not have an increased risk of cancer, and the increased risk estimates for some specific cancer sites were not conclusive.